Comparison of the separation of proteins of wide‐ranging molecular weight via trilobal polypropylene capillary‐channeled polymer fiber, commercial superficiously porous, and commercial size exclusion columns. Issue 9 (2nd March 2022) - Huang, Sisi; McClain, Ray T.; Marcus, Richard Kenneth
Abstract: Reversed phase and size‐exclusion chromatography methods are commonly used for protein separations, although they are based on distinctly different principles. Reversed phase methods yield hydrophobicity‐based (loosely‐termed) separation of proteins on porous supports, but tend to be limited to proteins with modest molecular weights based on mass transfer limitations. Alternatively, size‐exclusion provides complementary benefits in the separation of higher mass proteins based on entropic, not enthalpic, processes, but tend to yield limited peak capacities. In this study, microbore columns packed with a novel trilobal polypropylene capillary‐channeled polymer fiber were used in a reversed phase modality for the separation of polypeptides and proteins of molecular weights ranging from 1.4 to 660 kDa. Chromatographic parameters including gradient times, flow rates, and trifluoroacetic acid concentrations in the mobile phase were optimized to maximize resolution and throughput. Following optimization, the performance of the trilobal fiber column was compared to two commercial‐sourced columns, a superficially porous C4‐derivatized silica and size exclusion, both of which are sold specifically for protein separations and operated according to the manufacturer‐specified conditions. In comparison to the commercial columns, the fiber‐based column yielded better separation performance across the entirety of the suite, at much lower cost and shorter separation times.